Dimensions of Relations between the Kurdistan Region of Iraq with the Kingdom of Saudi Arabia and Turkey (2014-2018) - Sarsam Khaleel omar; Sabah Subhihayder; Mohammad H.AL-Katatsheh (QALAAI ZANIST SCIENTIFIC JOURNAL, 2021)
The Kurdistan Region of Iraq as a federal region within Iraq after the uprising and the formation of the Kurdistan Regional Government in 1992 is trying to strengthen its political, economic and cultural relations with the international community, especially with neighboring countries, including Saudi Arabia and Turkey, to ensure the promotion of peace, stability, political, economic and cultural development, especially in the period 2014-2018. After the emergence of an armed terrorist group called the Islamic State in Iraq and the Sham (ISIS) and the war on this group as it creates a new reality for the Kurdistan Regional Government through which the direct confrontation between ISIS and the Kurdistan Region became direct, where the Peshmerga forces were able to repel the terrorist attacks at the beginning of the matter and then Later, it was able to regain some areas that were before the events of 11/6/2014 It is located outside the security control of the Peshmerga forces with the aid of the International Coalition Forces against (ISIS). Nevertheless, the Kurdistan Region managed to host about 1,800,000 displaced Syrians and refugees, which led to an increase in the region’s population by 30%, and the subject of the Kurdistan Region’s referendum towards independence in September 2017, without a doubt. The events have a profound effect on changing the region’s relations with countries in the world, especially with the Kingdom of Saudi Arabia and Turkey, from here the importance of the political, economic and religious dimension in the scope of the role of political elites and rulers in the Kurdistan Region – Iraq.